DETERMINAN KEPUASAN KONSUMEN SERTA IMPLIKASINYA TERHADAP LOYALITAS KONSUMEN PADA MAKANAN FRANCHISE DI DKI JAKARTA - Elli Sulistyaningsih; Wahyu Murti; Arni Kurniati; Chrisindi (Universitas Borobudur, 2023)
This study aims to examine the effect of service quality and product quality on customer satisfaction and the implications for customer loyalty from franchise restaurant. The research was conducted using a quantitative approach and the sampling technique used was cluster sampling with a total of 111 respondents. Data was obtained through a questionnaire distributed to visitors to the franchise restaurant. The results showed that service quality and product quality have a significant influence on customer satisfaction and customer loyalty. Service quality has a greater influence on customer satisfaction than product quality. In addition, consumer satisfaction also has a significant influence on consumer loyalty. The implication of this research is the importance of restaurant managers in improving the quality of service and products served to achieve customer satisfaction and build strong customer loyalty. In the restaurant business, customer satisfaction is very important because satisfied customers will come back and recommend the restaurant to others. Therefore, restaurants must ensure that the quality of service and products served can meet consumer expectations.